The birds of Sangihe and Taluad , North Sulawesi - Riley, Jon (KUKILA, 1997)
The islands of Sangihe, Siau and Talaud were visited between 24 August and 31 October 1995 and a total of 126 species recorded. This paper provides details of all species recorded, including those new to the islands, additional information is provided on the five endemic species: Eos histrio, Loriculus catamene. Halcyon enigma, Eutrichomyias rowleyi and Aethopyga duyvenhodei. Further details are provided of records made between 1986 and 1995 during visits to the islands by four individual birdwatchers. Four of the endemic species were shown to be more common than previously thought, whilst details of the third record of Eutrichomyias rowleyi are presented. The conservation status of the islands is discussed and recommendations made for future research.